2021
DOI: 10.1021/acsinfecdis.0c00863
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Function Potentiation by PEG-BPEI Restores Activity of Carbapenems and Penicillins against Carbapenem-Resistant Enterobacteriaceae

Abstract: The rise of life-threatening carbapenem-resistant Enterobacteriaceae (CRE) infections has become a critical medical threat. Some of the most dangerous CRE bacteria can produce enzymes that degrade a wide range of antibiotics, including carbapenems and β-lactams. Infections by CRE have a high mortality rate, and survivors can have severe morbidity from treatment with toxic last-resort antibiotics. CRE have mobile genetic elements that transfer resistance genes to other species. These bacteria also circulate thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
(187 reference statements)
0
11
0
Order By: Relevance
“…This leads to the development of multi‐drug resistant CRE [23] . In addition to the anti‐biofilm results presented in this manuscript, PEG‐BPEI has been shown to render the CRE strains K. pneumoniae ATCC BAA‐2146 and E. coli ATCC BAA‐2452 more susceptible to the carbapenem antibiotics meropenem and imipenem by reducing the MIC to values below the resistance breakpoints [10d] . Because of these results, and the ability of PEG350‐BPEI to disrupt biofilms and antibiotic resistance in Pseudomonas aeruginosa and Staphylococci , [11,25] new technological pipelines are opened to address drug‐resistant pathogens and biofilm formation that place a significant burden on the health care system [24d,26]…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This leads to the development of multi‐drug resistant CRE [23] . In addition to the anti‐biofilm results presented in this manuscript, PEG‐BPEI has been shown to render the CRE strains K. pneumoniae ATCC BAA‐2146 and E. coli ATCC BAA‐2452 more susceptible to the carbapenem antibiotics meropenem and imipenem by reducing the MIC to values below the resistance breakpoints [10d] . Because of these results, and the ability of PEG350‐BPEI to disrupt biofilms and antibiotic resistance in Pseudomonas aeruginosa and Staphylococci , [11,25] new technological pipelines are opened to address drug‐resistant pathogens and biofilm formation that place a significant burden on the health care system [24d,26]…”
Section: Discussionmentioning
confidence: 64%
“…The reasons for this observation are unclear. Nevertheless, the aim of this work was to disperse E. coli biofilms with the same agent that disables CRE antibiotic resistance mechanisms [10d] . Additionally, in a clinical setting, wounds are likely to be contaminated with multiple bacterial strains and/or species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… , , However, the toxicity concerns arising from the presence of primary amines 600 Da BPEI are significant and need to be addressed. The in vivo toxicity concerns are resolved by covalently conjugating a low-molecular-weight polyethylene glycol (350 MW PEG) moiety to 600 Da BPEI, resulting in PEG-BPEI (Figure bottom). , Additionally, we have shown that the PEGylated derivative possesses the potentiator characteristics of BPEI against the MDR strains and their biofilms. , Regardless of the BPEI ability to facilitate the uptake of drugs and lower drug influx barriers as an antibiotic potentiator against bacterial biofilms and planktonic cells, therapeutic benefits of 600 Da BPEI and PEG-BPEI can be expanded. In this work, we continue to investigate 600 Da BPEI and its PEGylated derivative as anti-PAMP molecules to help mitigate the overproduction of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified low molecular weight 600 Da branched polyethylenimine (600 Da BPEI) as a broad-spectrum antibiotic potentiator that can overcome antibiotic resistance and restore the susceptibility of MDR strains of Gram-positive and Gram-negative bacteria to existing antibiotics. We have also reported its antibiofilm properties and suggested that the cationic nature of BPEI enables electrostatic interactions with anionic targets in biofilms. However, the primary amines of 600 Da BPEI create cytotoxicity concerns that cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%